To Call or Not to Call a Spade a Spade: The Dilemma of Treating 'Offensive' Terms in Duramazwi Guru reChiShona - Chabata, Emmanuel; Mavhu, Webster M. (Lexikos, 2005)
ABSTRACT: As noted by Béjoint (2000: 6), the main objective in dictionary-making is to define words and terms. This is especially the case if the fact is accepted that dictionaries are mostly con-sulted for word meaning and that, in the consultation process, the user hopes to acquire and/or verify certain information. However, as again noted by Jackson (1988), Landau (1984), Svénsen (1993) and Zgusta (1971), among others, the description of word meaning is one of the greatest difficulties with which the lexicographer has to cope. This article discusses some of the challenges facing lexicographers when defining 'offensive' headwords in a monolingual dictionary. It is based on experiences of defining such headwords for the general-purpose, medium-sized, synchronic, monolingual Shona dictionary, Duramazwi Guru reChiShona (henceforth DGC) (Chimhundu et al. 2001). DGC was compiled and edited by a six-member team of mother-tongue speakers of Shona who are researchers at the African Languages Research Institute (ALRI). The article also discusses some of the strategies the team of editors adopted as ways of dealing with offensive words in DGC. One such strategy is the use of euphemism in defining.Keywords: ALRI, CULTURE, DEFINITION, THEORETICAL DEFINITION, PRACTICAL DEFINITION, DICTIONARY, EUPHEMISM, LEXICOGRAPHY, MONOLINGUAL DICTION-ARY, OFFENSIVE HEADWORD, SHONA*****OPSOMMING: Om die kind by sy naam te noem of nie te noem nie: Die dilemma van die behandeling van "aanstootlike" terme in Duramazwi Guru reChiShona. Soos deur Béjoint (2000: 6) opgemerk, is die hoofdoel van woordeboekmaak om woorde en terme te definieer. Dit is veral die geval as die feit aanvaar word dat woordeboeke meestal geraadpleeg word vir woordbetekenis en dat, by die raadplegingsproses, die gebruiker hoop om sekere inligting te bekom en/of te kontroleer. Soos weer eens opgemerk deur onder andere Jackson (1988), Landau (1984), Svénsen (1993) en Zgusta (1971), is die omskrywing van woordbetekenis egter een van die grootste moeilikhede wat die leksikograaf moet hanteer. Hierdie artikel bespreek sommige van die uitdagings waarvoor leksikograwe te staan kom wanneer "aanstootlike" trefwoorde in eentalige woordeboeke gedefinieer word. Dit is gebaseer op die ervarings by die definiëring van sulke trefwoorde vir die meerdoelige, mediumgroot, sinchroniese, eentalige Sjonawoordeboek, Duramazwi Guru reChiShona (voortaan DGC) (Chimhundu et al. 2001). DGC is saamgestel en geredigeer deur 'n span van ses moedertaalsprekers van Sjona wat navorsers by die African Languages Research Institute (ALRI) is. Die artikel bespreek ook sommige van die strate-gieë wat die redakteurspan gekies het as maniere om aanstootlike terme in DGC te behandel. Een so 'n strategie is die gebruik van eufemismes by definiëring.Sleutelwoorde: ALRI, KULTUUR, DEFINISIE, TEORETIESE DEFINISIE, PRAKTIESE DEFINISIE, WOORDEBOEK, EUFEMISME, LEKSIKOGRAFIE, EENTALIGE WOORDEBOEK, AANSTOOTLIKE TREFWOORD, SJONA